A ratiometric fluorescence aptasensor based on photoinduced electron transfer from CdTe QDs to WS2 NTs for the sensitive detection of zearalenone in cereal crops. (15th August 2022) - Bi, Xiaoya; Li, Libo; Luo, Lijun; Liu, Xiaohong; Li, Jiamin; You, Tianyan
Highlights: WS2 NTs quenched the fluorescence of CdTe QDs via photoinduced electron transfer. A ratiometric fluorescence aptasensor was developed to detect ZEN. Exo I was introduced to digest the single-strand aptamer without ZEN. The aptasensor showed programmable sensitivity, superior accuracy and reliability. Abstract: Semiconductor quantum dots (QDs) and tungsten disulfide nanosheets (WS2 NTs) have been widely studied in photocatalysis and photoelectrochemistry as representative electron donor–acceptor pairs but rarely in fluorescence sensing. In this study, we investigated the effect of WS2 NTs on the fluorescence signal of cadmium telluride (CdTe) QDs by grafting an aptamer as a bridge between them. The corresponding quenching mechanism was systematically explored, and results described the photoinduced electron transfer (PET) from excited CdTe QDs to WS2 NTs. Based on these results, a novel ratiometric fluorescence aptasensor was developed for zearalenone (ZEN) determination by innovatively introducing exonuclease I to digest the aptamer of ZEN and control the PET between CdTe QDs and WS2 NTs. The designed aptasensor exhibited an acceptable linear range and detection limit (0.1 pg mL −1 ), and superior accuracy and selectivity. This ratiometric fluorescence aptasensor was also used to monitor ZEN in rice and corn flour.